Determinants of dairy contract farming adoption and differences in household food insecurity among smallholder farmers in Malang, East Java - Aminah Happy Moninthofa Ariyani; Mohammad Wahyu Firdaus; Taufik Rizal Dwi Adi Nugroho; Mardiyah Hayati; Desi Ramadhani; Moh. Rizal; Syauqi Agung Firmanda (Agriekonomika, 2025)
Food insecurity remains a persistent challenge among rural agricultural households, particularly among smallholder farmers whose livelihoods depend on unstable agricultural markets and limited institutional support. In dairy-producing regions of Indonesia, contract farming has emerged as a potential institutional mechanism to improve farmers’ market access and stabilize income. However, empirical evidence on how participation in dairy contract farming affects household resilience to food insecurity remains limited. Therefore, this study aims to analyze the factors influencing smallholder dairy farmers’ decisions to participate in contract farming and to examine differences in household food insecurity between contract farming participants and non-participants in Malang Regency, East Java. This study uses primary data collected from 100 smallholder dairy farming households through direct interviews using a multistage sampling technique in two dairy production centers: Pujon and Jabung. A Probit regression model was applied to analyze the determinants of contract farming adoption, and an independent-samples t-test was used to examine differences in household food insecurity, measured using the Food Insecurity Experience Scale. The results show that education and access to credit significantly influence farmers’ participation in contract farming. Education has a negative and significant effect, indicating that farmers with higher levels of formal education are less likely to participate in contract farming, whereas access to credit has a positive and significant effect, suggesting that financial resources facilitate farmers’ engagement in contractual production systems. Furthermore, the results reveal that dairy farmers participating in contract farming experience significantly lower levels of food insecurity compared to non-contract farmers. These findings highlight the importance of strengthening institutional market arrangements and improving farmers’ access to financial services to enhance the resilience of smallholder dairy farming households to food insecurity.